2012
DOI: 10.1177/1948550612466115
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Suicidality From Facial Appearance

Abstract: Suicide is a pervasive problem worldwide. In this investigation, we show that individuals can perceive suicidality from facial appearance with accuracy that is significantly greater than chance guessing. Inferences of expected or obvious cues, such as how depressed a person seems, did not lead to accurate judgments. Rather, perceptions of how impulsive an individual appears differentiated suicide victims from living controls. Teasing apart various forms of impulsivity revealed that perceptions of impulsive agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…More recent studies have suggested that faces alone express cues to depression (Scott et al 2013), and that people can determine who commits suicide from photos of suicidal and non-suicidal targets' faces (Kleiman and Rule 2013). Scott et al (2013) created composite faces (digital averages of multiple independent faces) of individuals who had scored high and low on a self-report measure of depression, finding that perceivers could perceive differences in depression from these computer-synthesized faces.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have suggested that faces alone express cues to depression (Scott et al 2013), and that people can determine who commits suicide from photos of suicidal and non-suicidal targets' faces (Kleiman and Rule 2013). Scott et al (2013) created composite faces (digital averages of multiple independent faces) of individuals who had scored high and low on a self-report measure of depression, finding that perceivers could perceive differences in depression from these computer-synthesized faces.…”
mentioning
confidence: 99%
“…Scott et al (2013) created composite faces (digital averages of multiple independent faces) of individuals who had scored high and low on a self-report measure of depression, finding that perceivers could perceive differences in depression from these computer-synthesized faces. Using more natural stimuli (yearbook and family photos), Kleiman and Rule (2013) found that individuals could distinguish people who had died by suicide from matched controls significantly better than chance and determined that perceptions of the targets' impulsive aggression supported this difference (though they did not have information about the individuals' actual impulsivity or aggression to corroborate these perceptions).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…State anxiety is more reliably detected in audio channels, whereas trait anxiety is more reliably detected in video channels (Harrigan et al, 2004). Even suicide attempts and outcomes can be predicted from thin slices Kleiman & Rule, 2013; see also Ekman & Friesen, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…A recent set of studies examined the ability to predict from just a face, whether a particular person committed suicide (Kleiman & Rule, 2013). This set of studies had the advantage of having an impressively larger sample size of targets.…”
Section: Suicidementioning
confidence: 99%